Implementasi Kebijakan Kota Layak Anak Pada Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Kota Palu - Anggita, Hasti Nabila Putri; Daswati; Farista, Gita (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
The purpose of this study is to give a clear image of how the Women's Empowerment and Child Protection Agency in Palu City is implementing child-friendly city policies and to pinpoint the variables that affect their effectiveness. The research methodology is descriptive and qualitative. The Palu City Women's Empowerment and Child Protection Agency (DP3A), the Social Agency, PATBM, the Nosarara Children's Forum, and non-governmental organizations (Libu Perempuan) served as the study's units of analysis. While data analysis procedures included data collecting, data reduction, data presentation, and conclusion drafting, data collection techniques included observation, interviews, documentation, and audio-visual materials. The KLA policy's execution in Palu City has not been ideal, according to research based on George C. Edward III's implementation theory. In terms of communication, information transmission between institutions is solid, but there is a gap in understanding at the field implementation level. In terms of resources, this policy is still hampered by budget constraints and supporting facilities. However, these weaknesses are compensated for by the commitment and high work ethic of the implementers. In terms of bureaucratic structure, the working mechanisms have a legal basis and standard operating procedures (SOPs), although crosssector coordination still needs to be simplified. Recommendations include the need to allocate a special budget for the provision of child-friendly facilities, simplify KLA educational materials for the general public, and optimize the role of PATBM at the village level. It is hoped that local governments can increase synergy so that the KLA policy does not merely become a bureaucratic procedure, but rather a participatory social movement.